Exploratory Studies on Land Holding Pattern and Adoption of Agroforestry Systems by the Farmers in Jabalpur District of Central India - Sharma, Aashutosh; Agarwal, Rasmi; Upadhayaya, S.D. (Indian Journal of Agroforestry, 2020)
An exploratorysurvey was conducted in seven blocks of Jabalpur district of central India. The farmers were selected purposively from all the blocks to know the land holding pattern and type of agroforestry system adopted by the farmers in their farmland. The inclination towards the adoption of agri-silvi-horticulture system was fairly higher (31 to 54%) by all the category offarmers. It is practically axiomatic that small and marginal farmers are more inclined towards diversified farming systems to fulfill their livelihood options.